Double poling muscle activation and fatigue during a simulated classic sprint cross-country skiing competition - Willis, S. I.; Hébert-Losier, K.; Andersson, E.; Holmberg, H. C.; Ortenblad, N. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The cross-country skiing double poling (DP) technique involves coordinated activation of both upper body (UB) and lower body (LB) muscles, especially for performance at high velocities (Holmberg et al., 2005; Lindinger et al., 2009). Little is known about UB and LB muscular activation and fatigue during a classic sprint competition, involving DP and diagonal stride (DIA). The aim of the study was to evaluate neuromuscular activation and fatigue during DP sections of a simulated sprint competition in elite athletes.